1988
DOI: 10.3171/jns.1988.69.3.0450
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between intraoperative SSEP's and postoperative function

Abstract: The authors report a case in which midline myelotomy for the removal of a C4-T4 ependymoma was immediately followed by abolition of short-latency somatosensory evoked potentials (SSEP's) in response to bilateral posterior tibial nerve (PTN) stimulation which proved irreversible intraoperatively. Subsequent intraoperative testing also revealed obliteration of median nerve (MN)-elicited responses. Postoperatively, joint and vibration sensations deteriorated in the lower extremities and there was unchanged very m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Owing to the sensitivity and specificity of SSEP monitoring, the incidence of postoperative paraplegia can be significantly reduced. 3,[7][8][9][10] However, a reliable intraoperative monitoring demands appropriate procedures of anesthesia, since the anesthetic itself, as well as accompanying hypothermia and hypotension, have a serious influence on evoked potentials. The depressant effect of volatile anesthetics on evoked potentials is well known.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the sensitivity and specificity of SSEP monitoring, the incidence of postoperative paraplegia can be significantly reduced. 3,[7][8][9][10] However, a reliable intraoperative monitoring demands appropriate procedures of anesthesia, since the anesthetic itself, as well as accompanying hypothermia and hypotension, have a serious influence on evoked potentials. The depressant effect of volatile anesthetics on evoked potentials is well known.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the rate of false-positive results with the use of SSEP monitoring averages 2%, with a reported range of 0 to 7%. [24][25][26][27] In 1992, the SRS issued a position statement advocating SSEP monitoring as the standard of care for scoliosis surgery. 28 A recent survey of 37 members of the Spinal Deformity Study Group of the SRS revealed that the mode of neuromonitoring in surgery for adolescent idiopathic scoliosis (AIS) varied on a case-by-case basis, with SSEP monitoring alone being used in 10% of cases, the wake-up test in 1.1%, and no IONM in 0.6%.…”
Section: ■ Clinical Tests Of Global Spinal Functionmentioning
confidence: 99%
“…2,3,7,[12][13][14][15] With compression or vascular compromise there tends to be involvement in multiple areas of the cord resulting in changes in the SSEPs that correspond to the damage. 2,3,7,[12][13][14][15] With compression or vascular compromise there tends to be involvement in multiple areas of the cord resulting in changes in the SSEPs that correspond to the damage.…”
Section: Spinal Cord Monitoringmentioning
confidence: 99%